HAZARDOUS ASPECTS AFFECTING PATIENT COMPLIANCE WITH FRAME CARE IN ILIZAROV SURGERY AT SINDH, PAKISTAN - KHAN, N; SIDDIQI, A; SIYAL, S; SHAIKH, MA; SHAIKH, A; LAGHARI, AR; SIYAL, FJ (Biological and Clinical Sciences Research Journal, 2023)
To assess risk factors affecting patient compliance and motivation and their interplay with adverse events affecting the outcome of Ilizarov surgery in a tertiary care hospital. The study was performed at the Orthopaedics Department, Liaquat National Hospital, Karachi, for 3 years (January 2014 to January 2017). The ethics review committee approved the study. During this period, 260 patients were operated with Ilizarov in our center. The mean age was 30 years. Factors examined include family income, living conditions, level of education, ethnic/cultural background, language barrier etc. Outcome measures were pin tract infection and treatment failure, such as abandoning treatment or amputation. Out of 193 patients, 148(76.6%) patients were males and 45(23.3%) patients were females. 44(22.7%) patients had underlying systemic diseases such as Hypertension and Diabetes mellitus. Out of 44 patients, 26(13.4%) patients had Hypertension and 18(9.3%) patients had Diabetes mellitus. Out of 193 patients, 157(81%) had favorable outcome whereas 37(19.1%) patients had unfavorable outcomes. Out of 37 patients, we had 28(75.6%) pin tract infections. Most were treated conservatively with antibiotics and dressings. There were 9(24.3%) patients with failure of treatment. The ethnic background of the patient, level of education, living conditions etc played a significant role in preventing developing pin tract infections and treatment failure.